Environmental Education and Evaluative Practice. Some Thoughts for the Construction of Eco-Consciousness [Educación Ambiental y Cultura Evaluativa. Algunas Reflexiones Para la Construcción de Eco-Consciencias] - Rios-Munoz, D; Herrera-Araya, D (Universidad Austral de Chile, 2017)
The purpose of this article is to reflect on the relationships and interactions between Environmental Education (EE) and the evaluative practice. The principal aim is to develop an evaluative proposal that contributes to the education of eco-conscious and eco-responsible people. The underlying premise states that the school is, nowadays, a privileged place to generate and introduce innovative educational practices that contribute to protect the environment. The main basis of this article is that the development of an evaluative practice of ecoconsciousness-oriented training in the classroom allows to improve and strengthen learning for life.